2021
DOI: 10.1353/pla.2021.0009
|View full text |Cite
|
Sign up to set email alerts
|

“We’re Gonna Figure This Out”: First-Generation Students and Academic Libraries

Abstract: Although extensive research has looked at first-generation college students' experiences, very little has examined the role of the library. This article reports the results of an asset-based exploratory study understanding the experiences of first-generation college students at three universities. Key findings of this study focus on themes of self-advocacy, sense of belonging, library customization, and integration of the library with the larger campus. This article discusses these key themes in the context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Of note, none of the CGS selected these agents. This FGS leaning aligns with Brinkman et al (2013) and Couture et al (2021) who find that they tend to look outside the libraries for research help. Brinkman et al (2013) state that they turn to "working-class university staff such as bus drivers, custodians, and cafeteria servers as another source of information and support" (p. 647).…”
Section: Building Social Capital First Year Of Collegesupporting
confidence: 84%
See 3 more Smart Citations
“…Of note, none of the CGS selected these agents. This FGS leaning aligns with Brinkman et al (2013) and Couture et al (2021) who find that they tend to look outside the libraries for research help. Brinkman et al (2013) state that they turn to "working-class university staff such as bus drivers, custodians, and cafeteria servers as another source of information and support" (p. 647).…”
Section: Building Social Capital First Year Of Collegesupporting
confidence: 84%
“…The library and information science (LIS) literature covers FGS' perceptions of libraries and librarians (Borrelli et al, 2018;Brinkman et al, 2013;Couture et al, 2021;LeMire et al, 2021a;Long, 2011;Pickard & Logan, 2013) as well as acquisition and assessment of their IL skills (Graves et al, 2021;LeMire et al, 2021b;Quiñonez & Olivas, 2020). Borrelli et al (2018) look at changes in FGS perceptions of library personnel over time.…”
Section: Libraries and First-generation Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Couture et al . found that “Students indicated their use of the library space was related to whether they felt welcomed and respected as individuals, including their identities as FGS [first-generation students] and all their intersecting identities.” (2021).…”
Section: Background/literature Reviewmentioning
confidence: 99%